(untitled) - Molles, Manuel C. (New York, 2008)
An introductory general ecology text featuring an emphasis on helping students grasp the main concepts of ecology. This book begins with the natural history of the planet, considers portions of the whole in the middle chapters, and ends with another perspective of the entire planet in the concluding chapter
Keywords: Ecology,Sinh thái học